DEVELOPMENT OF AN ELECTRONIC PUBLIC COMPLAINTS SYSTEM TO IMPROVE PUBLIC SERVICES - Sinlae, Alfry Aristo J; Daniarti, Yeni; Alamsyah, Dedy; Damuri, Amat (Jurnal Pilar Nusa Mandiri, 2022)
Public complaints are essential for the government to see how successful it is in carrying out activities. Public complaints are an essential element for local agencies because complaints are aimed at correcting the shortcomings of the activities that have been carried out. The absence of an electronic complaint system will hamper the complaint reporting process, so repairing deficiencies in government agencies will be hampered. The delay in repairing deficiencies in the agency will, of course, also affect the services provided to the community. The government can certainly use technology development to improve public services from the government to the community. This study discusses the development of an online-based public complaint system with the website-based Extreme Programming (XP) method that the public can access so that complaint reports can be submitted in real-time. The results of testing the complaint system from the usability side show an average value of 88.7% in the excellent category, so the application is feasible to use and as needed.